What does physiotherapy teach us about back pain? - O'Callaghan, Josephine (Henry Stewart Talks, 2015)
Physiotherapy as an intervention for lower back pain (LBP), Classifying LBP, Subjective assessment, Neurological evaluation, Movement assessment, Palpation & muscle testing, LBP management and therapy